Learning Jupyter : learn how to write code, mathematics, graphics, and output, all in a single document as well as in a web browser using Project Jupyter /: learn how to write code, mathematics, graphics, and output, all in a single document as well as in a web browser using Project Jupyter. (2016) - Toomey, Dan
No abstract available